Epigenetics in breast cancer - Atalay, C. (Experimental Oncology, 2013)
Epigenetic information has recently gained the attention of researchers and epigenetics in breast cancer is still an evolving area of research. Epigenetic modifications such as DNA methylation and histone acetylation have been thoroughly evaluated in breast cancer. New methods to detect epigenetic changes with higher specificity have been developed. These methods are utilized to find new markers for the diagnosis and prognosis of breast cancer. In addition, epigenetic modifications are assumed as new targets in the treatment of breast cancer and new drugs alone or in combination with conventional therapies such as chemotherapy or hormone treatment are being tested in clinical trials.